Deep-water Raphitomidae (Mollusca, Gastropoda, Conoidea) from the Campos Basin, southeast Brazil - Figueira, Raquel Medeiros Andrade; Absalão, Ricardo Silva (Zootaxa, 2012)
During the program “Environmental Characterization of the Campos Basin, RJ, Brazil”, carried out from 2001 to 2003,117 stations were sampled on the continental slope of the Campos Basin off southeast Brazil, by the Research Vessel“Astro-Garoupa”. The samples were taken on soft bottoms at depths from 700 to 1950 m, with a 0.25 m2 box corer or bydredging with a Charcot dredge. Mollusks were present at all of the stations, and among the Gastropoda the Conoideashowed the highest diversity. Here we present the results obtained for the most abundant family, Raphitomidae. We found21 species in eight genera: Famelica, Eubela, Xanthodaphne, Magnella, Gymnobela, Pleurotomella, Aliceia andNeopleurotomoides. The last two genera are reported here for the first time in the South Atlantic Ocean. Among the 21species two had been previously reported for this region: Magnella malmii (Dall, 1889) and M. extensa (Dall, 1881).Three species had been reported for Brazil, but the new finds expand their known geographical distribution: Eubelalimacina (Dall, 1881), Famelica mirmidina (Dautzenberg & Fischer, 1986) and Pleurotomella cala (Watson, 1885).Twelve species are reported for the first time in the South Atlantic: Aliceia aenigmatica Dautzenberg & Fischer, 1897,Xanthodaphne dalmasi (Dautzenberg & Fischer, 1897), Xanthodaphne araneosa (Watson, 1881), Magnella watsoni(Dautzenberg, 1889), Gymnobela chyta (Watson, 1881), G. atypha (Bush, 1893), Gymnobela bairdii (Verrill & Smith,1884), Gymnobela blakeana Dall, 1881, Pleurotomella perpauxilla (Watson, 1881), P. bureaui (Dautzenberg & Fischer,1897), P. cf. anceyi (Dautzenberg & Fischer, 1897) and P. coelorhaphe (Dautzenberg & Fischer, 1896). Four species arenew to science and are described here: Neopleurotomoides aembe, Xanthodaphne pichi, Gymnobela xaioca and Pleurotomella ybessa.